EFEKTIFITAS PEMBERIAN DAUN PEPAYA TERHADAP PENINGKATAN PRODUKSI ASI IBU NIFAS DI PMB ASMAWATI, S.ST - Yusika, Kiki (Journal of Midwifery Tiara Bunda, 2023)
Based on health data from Lebak district, the coverage of exclusive breastfeeding in Lebak district was (76.9%) in 2019. Meanwhile, in 2020 there was a decline with the number of exclusive breastfeeding in Lebak district amounting to (70%). In this case, there was a decrease of (6.9%) from 2019 to 2020. The lactagogum content in papaya leaves is a substance that can increase and facilitate breast milk production, besides that the sapoin and alkaloids in papaya leaves can influence the prolactin hormone so that it functions in increasing smooth process of expressing breast milk. This research aims to determine the effectiveness of giving papaya leaves to increase breast milk production for postpartum mothers in the independent practice of Midwife Asmawati, S.Tr in 2023. The design used in this research is a quasi-experimental design using a two group post test design. The samples taken were 30, so the total number of samples in this study was 30 respondents taken using the accidental sampling technique. The results of the research obtained a p value of 0.005, meaning that there is effectiveness in giving papaya leaves to increase breast milk production for postpartum mothers in independent midwife practice in 2023. Another variable that is most dominantly related to the smooth production of breast milk is the frequency of breastfeeding with a p value of 0.003.